Bulking for stress urinary incontinence in men: A systematic review. Issue 7 (18th July 2019) - Toia, B.; Gresty, H.; Pakzad, M.; Hamid, R.; Ockrim, J.; Greenwell, T.
Abstract : Aims: An updated literature review on outcomes in men treated with currently commercially available bulking agents was performed to determine whether this is a reasonable option in selected patients. Methods: The review adhered to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses framework of systematic reviews. A comprehensive search of PubMed, Medline, and Embase was undertaken. Abstracts were independently screened by two investigators to include men with stress urinary incontinence treated with a peri‐urethral injection of bulking agents currently available in the market. Results: Only eight original articles met the inclusion criteria. The bulking agents used were Macroplastique in five studies (total 123 patients), Opsys, Durasphere, and Urolastic in one study each (10, 7, and 2 patients, respectively). Only one study was randomized; Macroplastique vs AUS in men with mild or total incontinence. The included populations were heterogeneous and encompassed endoscopic, perineal, abdominal and laparoscopic prostate surgery as well as spinal cord injuries and urethral sphincter insufficiency. Significant dissimilarity was evident for the duration of incontinence (9‐108 months), mean volume of bulking agent used (2.3–13.5 mL), number of cushions (1‐5), depth and position of the cushions. The outcomes varied significantly, with reported dry rates between 0% and 83%. Outcomes were limited by relatively short follow‐up in most studies. Conclusion: Following initial enthusiasm and then dismay with collagen‐based compounds, sparse and heterogeneous literature data were produced on newer non‐migrating and nonabsorbable bulking agents. Some studies have suggested encouraging, if short term outcomes, however, future studies are needed in this field to support recommendations for widespread use.